Đang tải thanh công cụ tìm kiếm ...
Phép Tính Online

Dùng quy tắc biến đổi dấu rồi thực hiện các phép tính:

Dùng quy tắc biến đổi dấu rồi thực hiện các phép tính:

a)\({{4x + 13} \over {5x\left( {x - 7} \right)}} - {{x - 48} \over {5x\left( {7 - x} \right)}};\)

b)\({1 \over {x - 5{x^2}}} - {{25 - 15} \over {25{x^2} - 1}}\)

Hướng dẫn làm bài:

a) \({{4x + 13} \over {5x\left( {x - 7} \right)}} - {{x - 48} \over {5x\left( {7 - x} \right)}} = {{4x + 13} \over {5x\left( {x - 7} \right)}} + {{x - 48} \over { - 5x\left( {7 - x} \right)}}\)

\( = {{4x + 13} \over {5x\left( {x - 7} \right)}} + {{x - 48} \over {5x\left( {x - 7} \right)}} = {{4x + 13 + x - 48} \over {5x\left( {x - 7} \right)}}\)

\( = {{5x - 35} \over {5x\left( {x - 7} \right)}} = {{5\left( {x - 7} \right)} \over {5x\left( {x - 7} \right)}} = {1 \over x}\)

 b) \({1 \over {x - 5{x^2}}} - {{25 - 15} \over {25{x^2} - 1}} = {1 \over {x\left( {1 - 5x} \right)}} + {{25x - 15} \over { - \left( {25{x^2} - 1} \right)}}\)

\( = {1 \over {x\left( {1 - 5x} \right)}} + {{25x - 15} \over {1 - 25{x^2}}} = {1 \over {x\left( {1 - 5x} \right)}} + {{25x - 15} \over {\left( {1 - 5x} \right)\left( {1 + 5x} \right)}}\)

\( = {{1 + 5x + x\left( {25x - 15} \right)} \over {x\left( {1 - 5x} \right)\left( {1 + 5x} \right)}} = {{1 + 5x + 25{x^2} - 15} \over {x\left( {1 - 5x} \right)\left( {1 + 5x} \right)}}\)

\( = {{1 - 10x + 25{x^2}} \over {x\left( {1 - 5x} \right)\left( {1 + 5x} \right)}} = {{{{\left( {1 - 5x} \right)}^2}} \over {x\left( {1 - 5x} \right)\left( {1 + 5x} \right)}} = {{1 - 5x} \over {x\left( {1 + 5x} \right)}}\)